Integrated energy monitoring and visualization system for Smart Green City development: Designing a spatial information integrated energy monitoring model in the context of massive data management on a web based platform - Kim, S.; Shin, D.; Choe, Y.; Seibert, T.; Walz, Steffen (Elsevier BV, 2012)
U-Eco City is a research and development project initiated by the Korean government. The project's objective is the monitoring and visualization of aggregated and real time states of various energy usages represented by location-based sensor data accrued from city to building scale. The platform's middleware will retrieve geospatial data from a GIS database and sensor data from the individual sensory installed over the city and provide the browser-based client with the accommodated information suitable to display geo-location characteristics specific to the respective energy usage. The client will be capable of processing and displaying real time and aggregated data in different dimensions such as time, location, level of detail, mode of visualization, etc. The platform's middleware has been developed into an operative, advanced prototype, providing information to a Web-based client that integrates and interfaces with the Google Earth and Google Maps plug-ins for geospatially referenced energy usage visualization and monitoring.